2023
DOI: 10.1039/d3dt00441d
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic reduction of CO2 to CO by a series of organometallic Re(i)-tpy complexes

Abstract: A series of organometallic Re(I)(L)(CO)3Br complexes with 4'-substituted terpyridine ligands (L) has been synthesised as electrocatalysts for CO2 reduction. The complexes' spectroscopic characterisation and computationally optimised geometry demonstrate a facial...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…Similar to the structurally related [ReX(CO) 3 (bipy)], the UV-Vis spectra of [ReX(CO) 3 (terpy-κ 2 N)] display intense bands below 350 nm attributed to π→π* and n→π* intraligand (IL) transitions, along with moderate, broad absorption in the range of 350-450 nm largely assigned to MLCT excitations (Figure 2 and Table S4). This assignment was also supported by density functional (DFT) calculations [46][47][48].…”
Section: [Rex(co) 3 (Terpy-κ 2 N)]mentioning
confidence: 57%
See 4 more Smart Citations
“…Similar to the structurally related [ReX(CO) 3 (bipy)], the UV-Vis spectra of [ReX(CO) 3 (terpy-κ 2 N)] display intense bands below 350 nm attributed to π→π* and n→π* intraligand (IL) transitions, along with moderate, broad absorption in the range of 350-450 nm largely assigned to MLCT excitations (Figure 2 and Table S4). This assignment was also supported by density functional (DFT) calculations [46][47][48].…”
Section: [Rex(co) 3 (Terpy-κ 2 N)]mentioning
confidence: 57%
“…Distinctly from the Re(I) complexes with phenyl, naphtyl, and phenanthrenyl pendant groups, the complexes [ReCl(CO)3(R-terpy-κ 2 N)] with 9-anthryl (5 Cl ), 2-anthryl (6 Cl ), and 1-pyrenyl (7 Cl ) groups are non-emissive in the solid state, and their solution photophysical properties are strongly affected by the aryl substituent [61,62]. As supported by Further evidence for the formation of the 3 MLCT state in these systems was provided using fs-TA spectroscopy, carried out for the representative complexes [ReX(CO) 3 (R-terpyκ 2 N)] with phenyl (1 Cl , 1 Br ) and 1-naphtyl substituent (2 Cl ) [48,59,61], as well as timeresolved infrared spectroscopy performed for 1 Cl [63]. All these studies confirmed the formation of the 3 S5) were attributed to the halide contribution to the excited state [47].…”
Section: Phenyl and More π-Conjugated Hydrocarbon Groupsmentioning
confidence: 83%
See 3 more Smart Citations